A 3D-printed Arabidopsis thaliana root imaging platform. Issue 13 (17th May 2021) - Moussus, Michel; Meier, Matthias
Abstract : Here, we developed and characterized 3D printed microfluidic chip designs and materials for plant culturing. One general open microfluidic chip has been established for high-resolution live imaging of plant roots under changing microenvironments. Abstract : High-resolution live imaging promises new insights into the cellular and molecular dynamics of the plant root system in response to external cues. Microfluidic platforms are valuable analytical tools that combine the precise spatial and temporal control of culture conditions with live-imaging capabilities. However, complexity in the fabrication and operations of current plant microfluidic platforms limits their use to a few technologically-focused laboratories. Here, we design and characterize an easy-to-implement 3D printed open microfluidic platform for Arabidopsis thaliana roots. Our biocompatibility study identified a suitable material for the platform production and an established drought stress assay validates the reliability of our stereolithography (SLA)-based next generation RootChip.